COMPARATIVE ANALYSIS OF PERFORMANCE BETWEEN TRANS JOGJA & QBUZZ - , REIZA FITRIANA FAUZIE ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The current traffic condition in Yogyakarta is increasingly alarming. People choose to use their own private vehicle, and one of the main reasons is because the current public transportations are considered not adequate yet. In hope to solve these problems, Trans Jogja was launched, a Bus Rapid Transit (BRT) system modeled on the TransJakarta system. But, despite the innovative concept, it has a low cost recovery for only 30%. Groningen is a university city, with a quarter of the population are students. People used bicycle as their main transportation. The only urban public transportation is bus, which is operated by Qbuzz. The focus in this research is to compare the performance of Qbuzz and Trans Jogja, and then analyze them, with Qbuzz as the benchmark study. In this research, five indicators are taken into consideration: demand, operatorâs service, infrastructures, routes, and regulations. Qualitative research approach is chosen instead over quantitative research. Among many types of qualitative research, case study is used. The used data is secondary data, and after that the available data is being analyzed. Survey showed that the current public transport in Yogyakarta hasnât able to attract customer with private vehicle, but some customer may change to using Trans Jogja if thereâs improvement. In term of service, customers of Trans Jogja are already quite satisfied. The main concern of the customer for the service is the punctuality of the bus. Because of the limited available bus fleet, Trans Jogja has difficulties providing service to all urban area. The available routes are still taking too much time for the cycle time. There are a lot of spaces for Trans Jogjaâs improvement, using Qbuzz as the reference. However, not every facility available in Qbuzz can be implemented in Trans Jogja. The nature of Yogyakartaâs residents also needs to be taken into consideration.